2019
DOI: 10.1109/tpel.2018.2859194
|View full text |Cite
|
Sign up to set email alerts
|

Novel Space Vector Pulsewidth Modulation Strategies for Single-Phase Three-Level NPC Impedance-Source Inverters

Abstract: IEEE Transactions on Power Electronics Abstract-This paper presents new Space Vector Pulse-Width Modulation (SVPWM) strategies for a single-phase three-level buck-boost Neutral Point Clamped (NPC) inverter coupled with Impedance-Source (IS) networks. These strategies can be implemented for systems with any IS networks with neutral point. The case study system is based on the quasi-Z-source inverter with continuous input current. To demonstrate an improved performance, the strategies are compared with a tradit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…Another advantage of the qZS converter is the lower peak current of the transformer. The normalized value of the transformer peak current in the qZS converter can be calculated as follows: (13) Similar to that, it can be shown that the peak transformer current of the CS converter is double of the average input current: (14) Dependences (13) and (14) are compared in Figure 13. It can be appreciated from the figure that the qZS converter features up to a 70% lower transformer peak current, while the normalized transformer peak current of the CS converter is constant.…”
Section: Shmentioning
confidence: 94%
See 2 more Smart Citations
“…Another advantage of the qZS converter is the lower peak current of the transformer. The normalized value of the transformer peak current in the qZS converter can be calculated as follows: (13) Similar to that, it can be shown that the peak transformer current of the CS converter is double of the average input current: (14) Dependences (13) and (14) are compared in Figure 13. It can be appreciated from the figure that the qZS converter features up to a 70% lower transformer peak current, while the normalized transformer peak current of the CS converter is constant.…”
Section: Shmentioning
confidence: 94%
“…The calculation of the inductance value is exemplified in many papers [1,8,14,26,33]. The input power level, input voltage range, and the predefined input current ripple are completely sufficient to define the parameters of the magnetic components.…”
Section: Comparative Analysis Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In [20], the switching sequence was modified to balance neutral-point potential. A new SVM applied to a single-phase, 3L-NPC Z-source inverter with a reduced number of conversions, higher performance, and equally distributed switch losses among transistors was recently proposed in [21]. Reference [22] proposed an SVM scheme for a 3L-T-type quasi-Z-source inverter with the aim of reducing the value and slew rate of common-mode voltage.…”
mentioning
confidence: 99%
“…Z-source inverters (ZSIs) and quasi-Z-source inverters (qZSIs) were proposed for different applications. Existing solutions were reviewed in [10][11][12][13][14], and different relevant issues are addressed in [15][16][17][18][19][20]. However, recent research revealed evident drawbacks of the IS-based converters in terms of power density and efficiency [21][22][23].Split-source inverters (SPIs) [24,25] were proposed as another alternative solution.…”
mentioning
confidence: 99%